Gold‐Catalyzed Aminoalkenylation of β‐Amino‐1, n‐Diynols to Cycloalkyl‐, Piperidinyl‐ and Pyranyl‐Fused Pyrroles. Issue 9 (25th April 2016) - Kothandaraman, Prasath; Zhao, Yichao; Lee, Bo Ra; Le Ng, Clarrisa Jia; Lee, Jun Yi; Ayers, Benjamin James; Chan, Philip Wai Hong
Abstract: A synthetic method to prepare cycloalkyl‐, piperidinyl‐ and pyranyl‐fused pyrroles efficiently by gold(I)‐catalyzed dehydrative aminoalkenylation of β‐amino‐1, n ‐diynols under mild conditions at room temperature is described. Abstract :